2000
DOI: 10.1042/0264-6021:3480633
|View full text |Cite
|
Sign up to set email alerts
|

Possible interference between tissue-non-specific alkaline phosphatase with an Arg54→Cys substitution and a counterpart with an Asp277→Ala substitution found in a compound heterozygote associated with severe hypophosphatasia

Abstract: Tissue-non-specific alkaline phosphatase (TNSALP) with an Arg(54)-->Cys (R54C) or an Asp(277)-->Ala (D277A)substitution was found in a patient with hypophosphatasia [Henthorn,Raducha, Fedde, Lafferty and Whyte (1992) Proc. Natl. Acad. Sci. U.S.A.89, 9924-9928]. To examine effects of these missense mutations onproperties of TNSALP, the TNSALP mutants were expressed ectopically inCOS-1 cells. The wild-type TNSALP was synthesized as a 66-kDa endo-beta-N-acetylglucosaminidase H (Endo H)-sensitive form, and process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(69 citation statements)
references
References 13 publications
6
63
0
Order By: Relevance
“…We therefore concluded that TNSALP (1559delT-C506S ⁄ C521S ⁄ C577S) formed a noncovalently assembled dimer similarly to sTNSALP (Fig. 8B) and the wild type enzyme [12,13]. As expected, TNSALP (1559delT-C506S ⁄ C521S ⁄ C577S) was secreted threefold more than TNSALP (1559delT) (Fig.…”
Section: Replacement Of Three Cysteines With Serine Residues In the Csupporting
confidence: 65%
See 2 more Smart Citations
“…We therefore concluded that TNSALP (1559delT-C506S ⁄ C521S ⁄ C577S) formed a noncovalently assembled dimer similarly to sTNSALP (Fig. 8B) and the wild type enzyme [12,13]. As expected, TNSALP (1559delT-C506S ⁄ C521S ⁄ C577S) was secreted threefold more than TNSALP (1559delT) (Fig.…”
Section: Replacement Of Three Cysteines With Serine Residues In the Csupporting
confidence: 65%
“…8). At first glance this finding was quite puzzling as several missense TNSALP mutant proteins (R54C, N153D, E218G, D289V and G317D), which form similar highmolecular-mass aggregates in the transfected cells, exhibit no enzyme activity [10][11][12][13][14]. However, the substitution of cysteines for serines at position of 506, 521 and 577 of TNSALP (1559delT) provided a clue.…”
Section: Tnsalp (1559delt) Forms An Aggregate and Is Degradedmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the mutations p.A115V, p.A162T, p.D277A and p.F310L had residual TNSALP enzyme activity and were properly anchored on the membrane [20,21,22,23]. However, other mutations, including p.R54C, p.N153D, p.E218G, p.D289V, p.G317D and c.1559delT, did not exhibit any residual ALP activity, had defects in membrane-anchoring and seemed to accumulate in the RE/Golgi apparatus before degradation in the proteasome [21,24,25,26,27,28]. Kiminitsu Oda et al demonstrated that the p.A116T protein failed to fold properly and forms disulfide-bonded aggregates, though it was indeed capable of interacting with the WT and reaching the cell surface [18].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced activity of TNAP caused by missense mutations in the TNAP gene causes hypophosphatasia, a heritable form of rickets and osteomalacia (21,22). Moreover, partial reduction of TNAP activity and impairment of osteoblast maturation is observed in osteoblasts differentiated in vitro from precursor cells prepared from Znt5 Ϫ/Ϫ mice (23).…”
mentioning
confidence: 99%